HARGA DIRI DAN STRES KERJA PADA KARYAWAN PEMASARAN KARTU KREDIT DI JAKARTA - Rendra Afandi; Fellianti Muzdalifah (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstract The purpose of this study was to determine the effect of self-esteem toward work stress on credit card marketing employees in Jakarta. The population of this study were all of credit card marketing officer in Jakarta. That consist of 60 respondents. This study using quantitative methods with ex post facto research design and using accidental sampling techniques Data collection using the Rosenberg self-esteem scale and the scale of job stress that adapted from Susilo. Statistical analysis was used to test the hypothesis regression with SPSS 17.00. Based on the results of the data, obtained value of F= 14.680, p= 0.000 < 0.05 (significant) and the value effect (Adjusted R Square) variables of selfesteem on job stress is 0.202 (20.2%). So that it can be concluded that there is significant effect of self-esteem towards job stress on credit card marketing officer in Jakarta. Keywords : Self-esteem, job stress, credit card marketing officer